HUBUNGAN ANTARA NORMA HUKUM PAJAK DENGAN IMPLEMENTASI TAX AMNESTY DI INDONESIA - Agung, Dirga; Tangko, Lidwina Apriliana Allo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The tax amnesty policy is a fiscal legal instrument designed to increase tax compliance, expand the state revenue base, and return taxpayer funds to the country through a mechanism of forgiveness for past tax obligations. This study aims to analyze the relationship between the normative objectives of tax law, as reflected in legal and economic theories and principles, and the reality of tax amnesty implementation in Indonesia. It also examines the relationship between national legal politics and tax amnesty policy as a product of government policy. A juridical-normative and sociological approach shows that, normatively, the tax amnesty is based on the principles of justice, legal certainty, and benefit (Law No. 11 of 2016). However, empirically, its implementation emphasizes short-term fiscal interests rather than fostering taxpayer legal awareness. From a legal-political perspective, this policy represents a compromise between economic needs and legal legitimacy. While fiscally successful, it has not been optimal in achieving long-term tax justice and compliance. Structural and moral reforms are needed to balance das sein and das sollen